THE EFFECT OF PLANTING MEDIA AND ECOENZYME TREATMENT ON SHALLOT PRODUCTION - Luta, Devi Andriani; Siregar, Maimunah; Syam, Fariz Harindra (Research Journal of Agriculture (RJA), 2023)
The demand for shallots is consistently high throughout the year, but production heavily depends on cropping patterns. However, excessive use of inorganic fertilizers has led to decreased agricultural land productivity. To increase shallot production, it is necessary to maintain and improve soil quality through the provision of organic matter. This study aims to determine the effect of planting media and ecoenzyme treatment on shallot production. A factorial randomized block design was used with two treatment factors: planting media and ecoenzyme. Planting media included 100% topsoil (M0), topsoil (75%) + chicken manure compost (25%) (M1), topsoil (50%) + chicken manure compost (50%) (M2), and topsoil (25%) + chicken manure compost (75%) (M3). Ecoenzyme treatments consisted of 0, 10, 20, and 30 ml. Observations were made on wet tuber weight per plot (g), dry bulb weight per plot (g), and tuber diameter (mm). The results showed that the provision of planting media in the form of 75% topsoil + 25% compost responded well to shallot production. However, ecoenzyme treatment and the interaction between ecoenzyme and growing media had no significant effect on shallot production in terms of wet tuber weight per plot, dry bulb weight per plot, and tuber diameter.